Influência de retardante vegetal e densidade de plantas no crescimento, componentes da produção, produtividade e acamamento na soja - Linzmeyer Junior, Rodolfo (2006)
The soybean presents well-known importance in the national chain of production of grains, currently it is the main Brazilian agricultural product justifying investments in technology aiming at the increase of the yield and reduction of the adverse factors to the crop. Thus, the present work if considers to evaluate the effect of the vegetal retardant use in different densities of sowing on the growth, components of yield, productivity and fallen plant index in the crop of the soybean to cultivate CD 209. The experiment was developed in the Technological Center Coopavel in the city of Cascavel PR. For in such a way, no tillage system was become fullfilled. The experimental design was arranged in randomized complete blocks, with four replications, in factorial outline (6X2), being the treatments gotten for the combination of six levels of the vegetal retardant Etil Trinexapac (0,0 0,2 0,4 0,6 0,8 and 1,0 L ha-1) and two densities of sowing (14 and 18 plants M-1). Evaluations with frequency of 14 days had been carried through, from the 21 days after the emergency (DAE) until the full bloom of the crop, getting themselves the diameter of stem and the height of canopy of the plants. Also three destructive collections to the 35 had been carried through, 70 and 100 DAE for attainment of dry matter in the different parts of the plant and leaf area. In the harvest the components of the yield had been evaluated, productivity and fallen plant index. The vegetal retardant and the densities of sowing had influenced directly in the height and the diameter of stem of the plants. For dry matter, components of the yield, productivity and fallen plant index did not have influence; however the leaf area were influenced by the sowing density